Development of Crackers Using Purple Yam Flour: Physicochemical and Sensory Characterization - Ulyarti Ulyarti; Septina Yuri Cahyati; Dian Wulansari; Fitry Tafzi; Surhaini Surhaini; YG Armando; Nazarudin Nazarudin (Postgraduate, University of Mataram, 2023)
Purple yam tuber is known to contain a lot of bioactive components useful for human health. This study was conducted to utilize the tuber in form of purple yam flour for crackers processing and to understand the effect of purple yam flour concentration on the characteristics of crackers.Â A completely randomized design was applied using several concentrations of purple yam flour (0, 10%, 20%, 30%, 40%, and 50%) and 3 replications. The concentration of purple yam flour affects volume expansion, color values (L*, a*, and b*) and anthocyanin content of the crackers, but did not affect its water content and texture. The higher concentration of purple yam flour decreased volume expansion, L*, b*, and overall acceptance of the crackers, but increased the anthocyanin content and a* values.Â This research proposes that 30% purple yam flour shall be applied to partly substitute wheat flour in crackers processing.Â At this concentration, crackers were accepted by the panelist (like it slightly) and has hardness value 287.2 gF, L* 70.35, a* 11.12, b* 20.18, 2.5% water, and anthocyanin content 179.6 mg cyanidin3-glucoside equivalent/g.